20 years of researching stroke through audit. (August 2018) - Rudd, Anthony G; Hoffman, Alex; Paley, Lizz; Bray, Benjamin
Over the last 20 years, England, Wales and Northern Ireland have developed an audit programme that now encompasses nearly all patients admitted to hospital with a stroke. This article records and reviews some questions that have been answered using data from the audit: Is the rate of institutional care after rehabilitation a possible measure of outcome? Does stroke unit care in routine practice give the benefits shown in randomized controlled trials? How is the quality of stroke care affected by a patient's age and the time of their stroke? Do patient-reported measures match those obtained from the professionals recording of processes of care? How do the processes of care after stroke affect mortality? Is thrombolysis safe to use in patients over the age of 80? Do staffing levels matter? Does assessing the safety of swallowing really make a difference? Do clinicians make rational decisions about end-of-life care in patients with haemorrhage? Does socioeconomic status influence the risk of stroke, outcome after stroke and the quality of stroke care? How much does stroke really cost in England, Wales and Northern Ireland? The article concludes that this national audit has improved stroke care across the United Kingdom, has given answers to important questions that could not be answered in any other way and has shown that benefits found in research do generalize into real clinical benefits in day-to-day practice.